2021
DOI: 10.3390/jcm10112506
|View full text |Cite
|
Sign up to set email alerts
|

New Treatments for Atopic Dermatitis Targeting Skin Barrier Repair via the Regulation of FLG Expression

Abstract: Atopic dermatitis (AD) is one of the most common chronic, inflammatory skin disorders with a complex etiology and a broad spectrum of clinical phenotypes. Despite its high prevalence and effect on the quality of life, safe and effective systemic therapies approved for long-term management of AD are limited. A better understanding of the pathogenesis of atopic dermatitis in recent years has contributed to the development of new therapeutic approaches that target specific pathophysiological pathways. Skin barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 207 publications
0
14
0
2
Order By: Relevance
“…Thyssen and Kezic [80] provided an excellent overview of the multifactorial environmental and genetic causes of AD. An extensive review by Dębi ńska [81] describes treatments for AD currently approved or in clinical trials, with specific focus on factors that regulate expression of the filaggrin gene.…”
Section: Mutations That Cause Loss Of Filaggrinmentioning
confidence: 99%
“…Thyssen and Kezic [80] provided an excellent overview of the multifactorial environmental and genetic causes of AD. An extensive review by Dębi ńska [81] describes treatments for AD currently approved or in clinical trials, with specific focus on factors that regulate expression of the filaggrin gene.…”
Section: Mutations That Cause Loss Of Filaggrinmentioning
confidence: 99%
“…Skin barrier dysfunction is associated with the reduced production of terminal differentiation-associated molecules, such as FLG and LOR, that are crosslinked by TGM1 to create a stable cornified protein shell known as the CE [ 22 , 23 , 24 ]. Results of a previous study revealed that Lactobacillus rhamnosus fermentation broth, when added to human epidermal skin model cells grown in vitro, improved epidermal barrier function by increasing the expression levels of LOR and FLG mRNAs [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal skin barrier dysfunction and inflammation play key roles in the development of AD [ 49 ], and epidermal structural proteins such as FLG, LOR, and involucrin are key players in epidermal skin barrier formation [ 50 ]. FLG is a major cytoskeleton protein of the cornified envelope, and LOR is a main structural cornified envelope protein that constitutes 70–85% of total protein mass in the cornified layer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Involucrin is an assembly and scaffold protein of the cornified envelope [ 19 ]. Reduced expressions of these epidermal barrier proteins are major pathological characteristics in the skin of AD patients [ 50 ]. Reduced levels of FLG and LOR expressions are associated with barrier disruption and skin inflammation, weakening of the epidermal barrier function, and are also observed in inflamed skin [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%